2016
DOI: 10.1093/mnrasl/slw226
|View full text |Cite
|
Sign up to set email alerts
|

Missing Fe: hydrogenated iron nanoparticles

Abstract: Although it was found that the FeH lines exist in the spectra of some stars, none of the spectral features in the ISM have been assigned to this molecule. We suggest that iron atoms interact with hydrogen and produce Fe-H nanoparticles which sometimes contain many H atoms. We calculate infrared spectra of hydrogenated iron nanoparticles using density functional theory methods and find broad, overlapping bands. Desorption of H 2 could induce spinning of these small Fe-H dust grains. Some of hydrogenated iron na… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…For example, from experiments in microgravity, Kimura et al (2017) concluded that the probability of the formation of pure iron grains should be very low and that, consequently, iron should be bound in iron compounds or accreted as impurities on other grains in the ISM. Another hypothesis was pursued by Bilalbegović et al (2016) who calculated infrared absorption spectra of hydrogenated iron particles. From a variety of astronomical observations and related astrophysical modeling, several groups inferred that a large fraction of the iron in the ISM could be incorporated as inclusions in silicate grains (Zhukovska et al 2018;Westphal et al 2019;Zafar et al 2019).…”
Section: Comparison With Other Forms Of Ironmentioning
confidence: 99%
“…For example, from experiments in microgravity, Kimura et al (2017) concluded that the probability of the formation of pure iron grains should be very low and that, consequently, iron should be bound in iron compounds or accreted as impurities on other grains in the ISM. Another hypothesis was pursued by Bilalbegović et al (2016) who calculated infrared absorption spectra of hydrogenated iron particles. From a variety of astronomical observations and related astrophysical modeling, several groups inferred that a large fraction of the iron in the ISM could be incorporated as inclusions in silicate grains (Zhukovska et al 2018;Westphal et al 2019;Zafar et al 2019).…”
Section: Comparison With Other Forms Of Ironmentioning
confidence: 99%
“…From the fit of the Mg and Si edges and the related ζ Mg values, we can extrapolate that a large fraction of iron is expected to be in interstellar silicates, at least for the considered lines of sight. The solid form of the interstellar iron is still highly debated and among the forms of iron considered in literature there are oxides (Draine & Hensley 2013), metallic Fe (Westphal et al 2019), inclusions of Fe and FeS in silicate grains, freeflying iron particles (Zhukovska et al 2018), and hydrogenated iron nanoparticles (Bilalbegović et al 2017).…”
Section: Silicate Cationsmentioning
confidence: 99%
“…From the fit of the Mg and Si edges and the related ζ Mg values, we can extrapolate that a large fraction of iron is expected to be in interstellar silicates, at least for the considered lines of sight. The solid form of the interstellar iron is still highly debated and among the forms of iron considered in literature there are oxides (Draine & Hensley 2013), metallic Fe (Westphal et al 2019), inclusions of Fe and FeS in silicate grains, free-flying iron particles (Zhukovska et al 2018) and hydrogenated iron nanoparticles (Bilalbegović et al 2017). Future instruments, such as the coming X-ray Imaging and Spectroscopy Mission (XRISM, Tashiro et al 2018) and the future Athena X-ray mission (Nandra et al 2013;Barret et al 2016), will allow to simultaneously study the Mg and Si K-edges with the Fe K-edge, especially for high column-density lines of sight (Rogantini et al 2018).…”
Section: Silicate Cationsmentioning
confidence: 99%